Systemic Lupus Erythematosus and Pregnancy- An Uptodate Review - Kaur , Avleen; Singh, Karan Deep; Mohan, Gurinder; Khullar, Umang (Research Highlights in Disease and Health Research Vol. 6, 2023)
Systemic lupus erythematosus (SLE) is an autoimmune connective tissue disease that primarily affects women of reproductive age. Autoantibodies and immune complexes cause damage to a variety of organs and tissues. Women with SLE can have exacerbation of disease during pregnancy. SLE increases the risk of spontaneous abortion, preterm delivery, intrauterine growth retardation, preeclampsia, neonatal lupus, stillbirth, and intrauterine fetal death in pregnant women. The use of anticoagulants, steroids, and immunosuppressive agents during pregnancy poses a significant risk to both the mother and the fetus. A multidisciplinary approach, as well as close medical, obstetrical, and neonatal monitoring, results in the best possible outcome. The authors describe the successful management of an antenatal patient with positive antinuclear, anti-ds DNA, and antiphospholipid antibodies and a poor obstetric history. She had an emergency cesarean section and gave birth to a healthy female child.